No one is safe until everyone is safe: Direction régionale de santé publique de Montréal’s risk-based approach to multilingual crisis communication - María Sierra Córdoba Serrano (Revista de Llengua i Dret - Journal of Language and Law)
Canada’s multiculturalism is situated within a bilingual framework that often restricts Canada’s linguistic diversity, which goes beyond its official languages. The limitations of this framework were exposed by the COVID-19 pandemic, during which government-led crisis communication strategies were guided by the country’s multilingual reality and the risks associated with ignoring it. This article focuses on a case study that examines multilingual communication strategies and practices coordinated during the pandemic by the Direction régionale de santé publique de Montréal. Drawing on documentary evidence and semi-structured interviews, the article reveals that Santé publique Montréal integrated a multilingual approach into its emergency communication strategy after the first wave of the pandemic, which resulted in more translations of COVID-19 information, and the implementation of bottom-up communication practices in collaboration with community-based organisations to build trust. The article also shows that the pandemic paved the way for a risk-based approach to language management capable of helping us rethink multilingualism management in Canada and beyond.